PERBAIKAN MANAJEMEN PEMELIHARAAN DAN PELAYANAN KESEHATAN TERNAK DI DESA TIANYAR BARAT - K, Budaarsa; Budiasa, K. M.; Suarna, W.; Puger, A.W; Suasta, M.; Miwada, I.M. S. (Buletin Udayana Mengabdi, 2012)
The Community service that aims to improve the management of Bali swine breeding was held on August 18, 2012. Community service was conducted with extension methods and practice. The field team was divided into three groups and then visited the farmers in the respective fields. In practice, the field has made animal health by providing vitamins B complex and de-worming treatment pigs suffering from worms. Besides pigs, cows and chickens were also given the health services. A total of 50 male pigs and 68 female pigs had received treatment, whereas cows and chickens respectively 11 and 16. The system of raising livestock in the village of Tianyar Barat is very simple, namely traditionally extensive. Breeders need to pay attention to health and food animal herds so that growth can be better.